2020
DOI: 10.3390/rel11070332
|View full text |Cite
|
Sign up to set email alerts
|

Media Representations of Religion, Spirituality and Non-Religion in Australia

Abstract: Despite predictions of decline, religion has featured prominently in the public sphere and the media since the events of 11 September 2001. Previous research on media and religion in Australia post-September 11 has focused largely on its negative impacts, particularly on Muslim communities. This article, in contrast, examines media representations of religion, spirituality and non-religion on an ‘ordinary day’, of 17 September, over a three-year period in the city of Melbourne. Its findings reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 24 publications
5
14
0
Order By: Relevance
“…Similar trends and findings were revealed by the Melbourne component of the 'Religion on an Ordinary Day' (RoD) study (Weng and Halafoff 2020) and are further examined in this Worldviews Complexity in COVID-19 Times study. Weng and Halafoff (2020) in their study of Melbourne newspapers on September 17, in 2013September 17, in , 2014September 17, in and 2015, as part of the international RoD study, found that Christianity, Islam and Judaism received a high level of media attention in news stories and across genres, thereby reflecting their higher status in Australia, compared to other religions. This news coverage was often sensationalised and focused on controversies related to sexual abuse (Christianity, Judaism) or terrorism (Islam).…”
Section: Religious Diversity In Victoria and Australiasupporting
confidence: 77%
See 4 more Smart Citations
“…Similar trends and findings were revealed by the Melbourne component of the 'Religion on an Ordinary Day' (RoD) study (Weng and Halafoff 2020) and are further examined in this Worldviews Complexity in COVID-19 Times study. Weng and Halafoff (2020) in their study of Melbourne newspapers on September 17, in 2013September 17, in , 2014September 17, in and 2015, as part of the international RoD study, found that Christianity, Islam and Judaism received a high level of media attention in news stories and across genres, thereby reflecting their higher status in Australia, compared to other religions. This news coverage was often sensationalised and focused on controversies related to sexual abuse (Christianity, Judaism) or terrorism (Islam).…”
Section: Religious Diversity In Victoria and Australiasupporting
confidence: 77%
“…To locate news articles for this media analysis, selected keywords related to religion, spirituality and non-religion were applied in searches via Factiva, a print and digital newspaper database available through Deakin University's library. These keywords were informed by previous media research and adapted according to the purpose of this paper (Knott et al 2013;Weng 2019Weng , 2020Weng and Halafoff 2020). Knott et al (2013) applied a broad categorisation to the concept of 'religion' in their Media Portrayals of Religions and the Secular Sacred study, viewed through three categories of Conventional Religion, Common Religion and the Secular Sacred.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations